Global fisheries governance and case study of fisheries governance of Autonomous Region of European Union – Azores - Tomkova, Katerina (2019)
This article seeks to identify the key principles that should guide the definition of the Global Fisheries Governance and Management. A particular focus for this work has been the concept of participative governance and the co-management systems in which responsibility for management is shared between the world, regions, states and user groups, usually at the local level. Governance in the context of fisheries is divided in this article to three levels: the first dealing with issues of legal instruments, the second concerned with institutions and the third focusing on the construction of mechanism of management, in terms of economic, social and environmental values and principles to guide fisheries policy making along a consistent path of case study of fisheries governance in Azores.